PENGARUH KUALITAS SUMBER DAYA MANUSIA, FASILITAS KERJA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERDAGANGAN KOTA TEBING TINGGI - J. Najri Habibi; Nelfida .; M. Alam Warda Ritonga; Asniwaty .; Supriyono . (Universitas Islam Sumatera Utara, 2021)
This research discusses about the influences of quality of human resource, work facility and utilization of information technology on employees’ work productivity at Trade Office of Tebing Tinggi City. The aim of this research is to analyse influences of quality of human resource, work facility and utilization of information technology both partially and simultaneously on employees’ work productivity at the office. This is a quantitative research with total sampling technique. Sample is 83 employees. Results show that each independent variable; quality of human resource, work facility and utilization of information technology, partially influences employees’ work productivity positively and significantly. quality of human resource has tcount value 4,487 and level of significance 0.000, work facility has 2,219 and 0.034, and utilization of information technology has 2,246 and 0.032. Simultaneously, quality of human resource, work facility and utilization of information technology have significant and positive influences on employees’ work productivity at Trade Office of Tebing Tinggi City with Fcount value 23,863 and level of significance 0.000.